Systemic oxidative stress levels and their associations with the risk of neovascular age-related macular degeneration and treatment response - Maiko Abe; Hiroshi Kunikata; Naoko Aizawa; Masayuki Yasuda; Fumihiko Nitta; Toshiaki Abe; Toru Nakazawa (International Journal of Retina and Vitreous)
Abstract Purpose To investigate the association between oxidative stress (OS) and both the risk of neovascular age-related macular degeneration (nAMD) and the treatment response to intravitreal anti-vascular endothelial growth factor injections (anti-VEGF IVIs). Methods This retrospective study included 46 treatment-naïve nAMD eyes of 46 patients (26 male and 20 female) who received anti-VEGF IVIs with a “treat-and-extend” regimen following an initial loading phase for one year. The patients were divided into two groups according to the total number of anti-VEGF IVIs administered during the year: the “effective” group and the “resistant” group. OS was evaluated by diacron reactive oxygen metabolites (d-ROMs), biological antioxidant potential (BAP), and skin autofluorescence (SAF) at baseline. For comparison, 54 control subjects were recruited. Results There were no significant differences in d-ROM or BAP levels between control subjects and nAMD patients, regardless of sex, whereas SAF levels were higher in nAMD patients overall and in male nAMD patients than in controls (P < 0.001 for both). The effective and resistant groups included 30 and 16 eyes, respectively. Among the male nAMD patients, the effective and resistant groups had similar baseline characteristics, including age, smoking history, visual acuity, and central macular thickness; however, the resistant group had higher SAF levels (effective vs. resistant: 2.3 vs. 2.6 arbitrary units [AU]; P = 0.02). This finding was further supported by a multiple logistic regression analysis, which showed that the odds ratio for SAF was 1.57 per 0.1 AU increase (P = 0.01). Conclusion SAF levels were significantly higher in nAMD patients than in controls. The total number of anti-VEGF IVIs required over one year in male nAMD patients depended on SAF levels, suggesting that the SAF levels may serve as a potential biomarker for the response to anti-VEGF IVIs in nAMD.